Quality Assessment of Studies Included in Cochrane Oral Health Systematic Reviews: A Meta-Research - Sofi-Mahmudi, Ahmad (Int J Environ Res Public Health, 2021)
Objectives: To assess the Risk of Bias (RoB) and other characteristics of published randomised clinical trials within Cochrane oral health systematic reviews. Materials and methods: All the published clinical trials within Cochrane oral health systematic reviews until 1 June 2020 were identified and examined. RoB was assessed for all the included clinical trials according to the Cochrane review standards. The Overall Risk of Bias (ORoB) was defined in this study using Cochrane’s RoB tool-v2. Descriptive analyses were carried out to determine the frequency of each variable in the study sample. Results: Out of a total of 2565 included studies, the majority (n = 1600) had sample sizes of 50 or higher. Regarding blinding, 907 studies were labelled as double-blind. Among the various domains of bias, the performance bias showed the highest rate of high risk (31.4%). Almost half of the studies had a high ORoB, compared to 11.1% with a low ORoB. The studies that used placebos had a higher percentage of low ORoB (14.8% vs. 10.7%). Additionally, the double- and triple-blind studies had higher percentages of low ORoB (23.6% and 23.3%, respectively), while the studies with a crossover design had the highest percentage of low ORoB (28.8%). Conclusion: The RoB of oral health studies published as Cochrane reviews was deemed high.